Attitudes of intermediate phase learners, educators, and school governing bodies towards Xitsonga as medium of learning and teaching in Limpopo Province - Mona, M. J. (My University, 2015)
This research study dealt with specific aspects relating to attitudes of intermediate phase learners, educators, and SGB members towards Xitsonga as medium of learning and teaching in Limpopo. The statement of the study’s problem was articulated against clearly defined contexts. As a foundational slab for the study, the thesis deemed it fit and necessary to give the background to the problem on attitudes in general and language attitude in particular. When the foundation had been laid, the statement of the problem was clearly articulated so as to open a curtain on the niche and the exact problem the thesis sought to investigate. The aim of the study was derived from the title, finetuned in the niche and focused on clearly defined objectives which informed the research lanes the whole project operated in. The significance of the research project was not a stand alone entity, but spoke to the aim and objectives. The police officer of the thesis was the theoretical framework. It directed the process by means of indicating that mother-tongue education as an ideal practice should also be considered for the post foundation phase studies also in South Africa. On its wings, was the behaviourist theory. Unlike its counterpart the mentalist theory, the former was a vehicle through which the study elicited valuable data by observing the behaviour of the target subjects in the Mopani District. Without a well-indicated scope of the study, the investigation would had been too general to address a specific niche. The distinct niche of the thesis was further uncovered and demonstrated by the evaluation of literature survey of various studies on language attitudes in the country as well as the world over. The search design of the study was also a context against which the qualitative approach was used for data gathering instruments, and sampling process. The ethical considerations were clearly outlined and applied accordingly prior and during the data collection process. The thesis would had been incomplete if relevant and up to date literature review was not done. In order to contextualise the thrust of language attitudes among the target research respondents, Chapter Two provided a brief but inclusive overview of (vi) historical data. The data were evaluated against language attitude theories, home language instruction principles, attitudes towards a sample of three dominant Limpopo official languages (that is, Xitsonga, Sepedi and Tshivenḓa), completed research studies that focused on language attitudes, language policy matters and curricula development and implications from the first post apartheid Curriculum 2005 up to the current Curriculum and Assessment Policy Statement (CAPS). The review or survey ended up with a critical evaluation of the concept of multilingualism in South African schools against language attitudes, four periods of language policy in the RSA, as well as the language phenomenon from divine creation to date. Before the fieldwork was undertaken, description was made in some detail on how the research data were collected, possible limitations to the research exercise were spelt out, coupled with counter-measures taken to ensure reliability, validity and objectivity in collecting data, and how analysis and interpretation of research data were actualised. The analysis and interpretation of the research data elicited from learners, teachers, and SGB members yielded almost similar results. The majority of all the respondents across the Mopani District (an average of 80%), displayed very strong negative attitudes towards mother-tongue instruction at Intermediate Phase level. Though learners and teachers had challenges with the use of the source language in class, they still did not favour the target language medium. Only 20% of their counterparts favoured the mother-tongue medium. The volunteer system in the composition of parent component of the SGB members was discovered by the study to be a serious challenge. This challenge does not assist the institutions they are governing to be what they should be. Almost 100% of them exposed themselves through the research tool used that they were not performing the core duties they were expected to perform save signing cheques and solving petty disputes. In conclusion, relevant and appropriate recommendations were made to affected stakeholders. They were addressed mainly to: communities, managers, teachers, government, community leaders, academics, researchers and writers on ways and means of addressing the deep-seated negative attitudes towards Xitsonga as a medium of instruction at Intermediate Phase level of the Mopani District.
Thesis (Ph. D. (Language and Education)) -- University of Limpopo, 2014
Keywords: Mother tongue language; Xitsonga home language; Language and educacation policy; Native language; Xitsonga language; Language and education -- South Africa -- Limpopo; Language and languages -- Study and teaching